Effect of Waste Iron Scraps in the Removal of Total Phosphorus for Sewage Effluent - Soo Park, Jung; Duk Kim, Sung; Seung Dho, Hyon (International Journal of Engineering and Technology, 2018)
Background/Objectives: Total phosphorus (T-P) in effluents from sewage treatment plants (STP) causes the eutrophication of natural water. In nature, metal iron (Fe) can be oxidized to Fe2+ or Fe3+ oxidation states as well as combine with PO43- to produce the compound FePO4. Method/Statistical analysis: The process parameters for T-P removal efficiency was investigated using iron scrap filters on STP effluents. Finding: The results revealedÂ the removal efficiencies of T-P and PO43- were decreased as the filtration velocity was increased.Â At the condition ofÂ Â filtration velocity of 300m/d, T-P concentration and color intensity were suited to South Koreaâ€™s water quality regulation standard ofÂ 0.2 mg/L. Improvement/Applications: This filtration system can be used to small capacity waste water treatment plant, operation concerns and cost-benefits. Â